The Role of Using iPad Technology in Enhancing Students’ Motivation toward Learning the English Language - Tarazi, Ayat; Arafat , Suzan (EDU REVIEW. International Education and Learning Review / Revista Internacional de Educación y Aprendizaje, 2021)
This study aimed to find out the role of the iPad in enhancing students’ motivation towards learning the English Language. The findings of the study showed that there were improvements in the level of student’s performance during English classes. It also showed that there were positive attitudes towards using iPad in learning English from the parents’ perspectives. The results also showed that the total degree of teachers’ attitudes towards the use of iPad in motivating students towards learning the English language is dramatically increasing. Based on these results, the researchers recommended the Ministry of Education, and teachers of English to adopt the iPad as an educational tool in their teaching.